Sustainability Management in the Higher Educational System - Mohammad Jaradat; Marius-Anton Stupar (Ovidius University Annals: Economic Sciences Series, 2019)
The complex interface between globalization and promoting fundamental standards of labor enjoys increasing attention. The European public attention in connection with this fact reflects a much bigger understanding of the globalization impact, an interest much more pronounced towards the economic relations and the understanding of the fact that an important part of the population wants to gain something more than money. There is a universal recognition of the fundamental labor standards. In Europe is recognized that sustainable economic growth goes hand in hand with social cohesion – which means respect for fundamental labor standards – and that is fundamental for EU’s economic and social policy. From this perspective, the present article aims to highlight the importance of Romania’s employment policy in relation to the EU policy and the importance of investing in education from the perspective of sustainable development in the labor market in higher education, as well as especially the sustainability of the Romanian higher education itself.